Unique Complications of Venous Anastomotic Couplers: A Systematic Review of the Literature - Wu, Gerald J.; Loewenstein, Scott N.; Mailey, Brian A.; Sasor, Sarah; Cook, Julia; Hassanein, Aladdin H. (Journal of Reconstructive Microsurgery, 2020)
Background Anastomotic couplers expedite venous microvascular anastomoses and have been established as an equivalent alternative to hand-sewn anastomoses. However, complications unique to the coupler such as palpability and extrusion can occur. The purpose of this study was to perform a systematic review of the literature to assess complications distinct to the venous anastomotic coupler.Methods A Medline, PubMed, EBSCO host search of articles involving anastomotic venous couplers was performed. Studies involving arterial anastomotic couplers, end-to-side anastomoses, and reviews were excluded. Data points of interest were flap failure, venous thrombosis, hematoma, partial flap necrosis, infection, coupler extrusion, and coupler palpability.Results The search identified 165 articles; 41 of these met inclusion criteria. A total of 8,246 patients underwent 8,955 venous-coupled anastomoses. Combined reoperation rate was 3.3% and all-cause unsalvageable flap failure was 1.0%. Complications requiring reoperation included venous thrombosis (2.0%), hematoma (0.4%), partial flap necrosis (0.4%), and infection (0.3%). Eight patients had palpable couplers and 11 patients had extrusion of couplers (head/neck, hand, and feet) and required operative management.Conclusion Venous couplers remain an equivalent alternative to conventional hand-sewn anastomosis. However, venous coupler extrusion and palpability in the late postoperative period is a complication unique to anastomotic couplers, particularly in radiated head and neck, feet and hand free flaps. Removing extruded venous couplers is safe after tissue integration 3 weeks postoperatively. Coupler palpability and extrusion should be integrated into preoperative patient counseling and assessed in follow-up examinations.
Keywords: anastomosis; coupler; coupling; extrusion